6-Gingerol modulates proinflammatory responses in dextran sodium sulfate (DSS)-treated Caco-2 cells and experimental colitis in mice through adenosine monophosphate-activated protein kinase (AMPK) activation. Issue 10 (11th August 2015) - Chang, Kuei-Wen; Kuo, Cheng-Yi
Abstract : 6-Gingerol suppressed up-regulated production of proinflammatory cytokine in DSS-treated Caco-2 cells. Abstract : Background : 6-gingerol has been reported to have anti-inflammatory effects in different experimental settings. The present study aimed at evaluating the effect of 6-gingerol on dextran sodium sulfate (DSS)-induced barrier impairment and inflammation in vitro and in vivo . Methods : a differentiated Caco-2 monolayer was exposed to DSS and treated with different concentrations of 6-gingerol (0, 1, 5, 10, 50, and 100 μM). Changes in intestinal barrier function were determined using transepithelial electrical resistance (TEER). The anti-inflammatory activity of 6-gingerol was examined as changes in the expression of proinflammatory cytokine using quantitative real-time PCR. Western blotting was employed to determine the activation of adenosine monophosphate-activated protein kinase (AMPK). Mice with DSS-induced colitis were given different oral dosages of 6-gingerol daily for 14 days. Body weight and colon inflammation were evaluated, and level of proinflammatory cytokines in colon tissues was measured. Results : 6-gingerol treatment was shown to restore impaired intestinal barrier function and to suppress proinflammatory responses in DSS-treated Caco-2 monolayers. We found that AMPK was activated on 6-gingerol treatment in vitro . In animal studies, 6-gingerol significantly ameliorated DSS-induced colitis by restoration of body weight loss, reduction in intestinal bleeding, and prevention of colon length shortening. In addition, 6-gingerol suppressed DSS-elevated production of proinflammatory cytokines (IL-1β, TNFα, and IL-12). Conclusion : our findings highlight the protective effects of 6-gingerol against DSS-induced colitis. We concluded that 6-gingerol exerts anti-inflammatory effects through AMPK activation. It is suggested that 6-gingerol has a promising role in treatment of IBD.